2011
DOI: 10.1682/jrrd.2009.12.0192
|View full text |Cite
|
Sign up to set email alerts
|

Falls requiring medical attention among veterans with multiple sclerosis: A cohort study

Abstract: Abstract-The purpose of this study was to estimate the relative risk of an injurious fall requiring medical attention in veterans with multiple sclerosis (MS) compared with veterans without MS after controlling for sex, age, and healthcare use. The sample included 195,417 veterans treated at Veterans Health Administration (VHA) facilities in the Northwest United States in fiscal year 2008. We obtained information regarding MS diagnosis, injurious falls (operationalized as International Classification of Diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
50
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 31 publications
2
50
0
Order By: Relevance
“…The proportions of fallers and injurious fallers found in this study, 58% and 44%, respectively, for the entire sample are consistent with other studies of falls in people with MS. [1][2][3][4]7,11,[22][23][24][25] However, the US sample fell more (72% fallers) than has been found in previous studies and more than the Australian sample, despite on average being less disabled and younger than the Australian sample. The reasons for this difference are uncertain but may be related to younger age, which has been found to be associated with increased fall risk in MS, 26 or to other unmeasured differences in the samples or in health-care delivery between countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportions of fallers and injurious fallers found in this study, 58% and 44%, respectively, for the entire sample are consistent with other studies of falls in people with MS. [1][2][3][4]7,11,[22][23][24][25] However, the US sample fell more (72% fallers) than has been found in previous studies and more than the Australian sample, despite on average being less disabled and younger than the Australian sample. The reasons for this difference are uncertain but may be related to younger age, which has been found to be associated with increased fall risk in MS, 26 or to other unmeasured differences in the samples or in health-care delivery between countries.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] More than 50% of people with MS fall in a 3-to 6-month period, and approximately 30% to 50% fall multiple times. [4][5][6] Falls in people with MS are associated with injuries 3,7,8 and adversely affect quality of life. 9 Fall risk in MS is generally attributed to impairments in the wide range of functions affected by the disease, including balance, cognition, vision, muscle strength and tone, coordination, and sensation.…”
mentioning
confidence: 99%
“…1 The Department of Veterans Affairs (VA) health-care system treats approximately 16,000 veterans with MS each year. 2 MS is a chronic disease that results in an annual cost burden of $8500 to $54,000 per patient in the United States, much of it from complications secondary to MS. 3,4 Two recent studies have demonstrated an increased risk of infection-related hospitalizations and infectionrelated mortality in patients with MS compared with those without MS in Sweden and the United Kingdom. 5,6 The objective of this study was to examine the risk of hospitalization and death due to infections in patients with and without MS in a cohort of US veterans.…”
mentioning
confidence: 99%
“…
Multiple sclerosis (MS) is a chronic neurologic disease that may cause impairments in cognition, muscle strength, muscle tone, sensation, coordination, balance, and gait, all of which are associated with an increased risk of falls.1-7 A number of studies also demonstrate that people with MS fall frequently 1,3,5,6,[8][9][10][11][12] and fall significantly more often than healthy people of the same age and gender.11,13 Over 50% of people with MS fall in a 3-to 6-month period, and around 30% to 50% fall multiple times. 3,[5][6][7]9,10 People with MS also often sustain fallrelated injuries.
…”
mentioning
confidence: 99%
“…1-7 A number of studies also demonstrate that people with MS fall frequently 1,3,5,6,[8][9][10][11][12] and fall significantly more often than healthy people of the same age and gender.…”
mentioning
confidence: 99%